Knowledge, Attitude, and Practice of Sports Nutrition among Adolescent Indian Kabaddi Players - Majumder, Sneha; Das, Debojyoti; Menon, Kavitha (Journal of Sports Research, 2022)
Kabaddi is an emerging sport in India that has gained immense importance after the victory at Asian games. The adolescent Kabaddi players are at their growth spurt, thus nutritional requirements are at peak. Thus, a cross sectional study was designed to explore the determinants of sports nutrition Knowledge, Attitude and Practice (KAP) among adolescent Kabaddi players (n=156) at Sports Authority of India, Gandhinagar. The Mean±SD scores of knowledge, attitude and practice were 5±1.7, 5±1.6 and 5.1±1.5, respectively. Coaches imparted nutrition information to most of the players (76.3%). Knowledge scores were significantly correlated to practice (P=0.004). The females and rural residents had significantly higher nutrition knowledge and practice than males and urban players, respectively. Older adolescents, and players with secondary and above education had better attitude scores. Multivariate analysis showed that mother’s educational status predicted the knowledge scores (P=0.01) and inversely practice scores (P=0.02). The study underscores the need for nutrition education to players that would translate to healthier food choices and better sports performance.